Integrating libqual and kano model for library service excellence / Voon Boo Ho - Boo Ho, Voon; Melvin Jussem, Petricia; Nity Mathew, Vloren (Universiti Teknologi Mara Cawangan Sarawak, 2013)
The proposed research aims to integrate the LibQUAL and Kano Model to identify the service attributes which will be useful for library service quality improvement towards excellence. The research will involve the identification of current service attributes (e.g. from LibQUAL), measuring user opinions on functional/dysfunctional attributes then categorizing the attributes based on Kano Model. The user satisfaction will also be measured so as to identify the strong and weak attributes. The strengths and weaknesses of the library service will be categorized (i.e., Must-be, One-dimensional, Indifferent and Attractive) in order to suggest for Maintain, Further development for innovative processes, and Improve. The library service quality, emotional experience, user satisfaction and behavioural intentions will also be investigated.